Evolutionary design of conductive pathways using a generative autoencoder - Ignuta-Ciuncanu, Matei C.; Stärk, Hannes; Martinez-Botas, Ricardo F. (International communications in heat and mass transfer, 2025)
To enhance performance and energy efficiency in compact electronic systems, effective thermal management through miniaturized heat sinks is essential. This study introduces a generative design framework for optimizing bi-material heat sink architectures suitable for space-constrained electronics. Conventional thermal optimization methods often rely on gradient-based techniques or parametric geometric shapes, which limit adaptability and design resolution. In contrast, our approach integrates topology optimization, constructal theory, and bio-inspired principles via a generative model that couples a variational autoencoder with evolutionary algorithms. Trained on a diverse dataset of microleaf structures, constructal patterns, and synthetic conductive networks, the model addresses the area-to-point conduction challenge, a common scenario where heat must be efficiently transferred from a broad source area to a narrow sink. Compared to standard methods, the proposed design pipeline reduces average device temperatures by 10% and peak hotspot temperatures by up to 1%. Additionally, it achieves a 13% increase in Pareto front hypervolume, indicating superior trade-offs among conflicting thermal objectives. By enabling smooth feature transitions and adaptive geometries through latent space interpolation, the method supports modular and scalable design of unit cells and full assemblies. A demonstrative case assembles these cells into a manufacturable three-dimensional heat sink tailored for spatially varying thermal loads. The methodology can extend beyond conductive heat sinks to encompass conjugate heat transfer and multi-physics systems by adjusting design objectives or finite element formulations. This work offers a blueprint for generative thermofluids design in applications such as phase-change materials, heat pipes, and cold plate systems. [Display omitted]